DIGITAL MARKETING STRATEGY TO INCREASE BRAND AWARENESS AND TRUST OF CUSTOMER OF ALL TOUR AND TRAVEL (The Indonesian Journal of Business Administration, 2019)
This research explain about digital marketing strategy of ALL Tour and Travel (ATT) to increase brand awareness and trust from customer. This research uses several analytical tools to examine the internal and external conditions, the analysis tools used are: Digital Marketing, Marketing Mix, STP Analysis for internal analysis. Then to find out external condition, the analytical tools used are: PEST Analysis, Industry Analysis, Consumer Analysis, and Competitor Analysis. Continued using SWOT analysis and Root Cause Analysis diagram. From the results of the research, there are four problem that ATT faced, such as Lack of brand awareness and product knowledge, not optimal use of digital platforms and social media, and lack of content marketing communication. The solution to this research uses TOWS Analysis, to identify problems and formulate strategies to solve the problem. The implementation of strategies to solve these problems are optimizing the digital marketing platform which includes website redesign, optimization of SEO and SEM, social media, and email marketing. Then to increase brand awareness through content marketing, including social media, photos, videos and collect testimonials. Next, to determine the priority of the implementation of the strategy is carried out using the urgency analysis of the Situation Appraisal Kepner-Tregoe Approach.Keywords: Digital Marketing Strategy, Brand Awareness, Customer Trust, Situation Appraisal, Travel Business.